Profesionalisme Guru dalam Meningkatkan Mutu Pendidikan Nasional: Studi Literatur - Tiarnita M. S Siregar; Feni Rahmadani Purba; Jesika Dana Lumban Batu; Wanta Mikhael Sihombing; Ilham Yusuf (Jurnal Keluarga Sehat Sejahtera, 2026)
Objective: This study aims to analyze the role of teacher professionalism in improving the quality of national education through a literature review approach. Method: This research employed a qualitative descriptive method using library research. Data were collected from scientific journals, books, research articles, and educational policy documents published within the last ten years. The data were analyzed using content analysis techniques to identify important findings related to teacher professionalism and educational quality. Results: The findings indicate that teachers have strategic roles not only as transmitters of knowledge but also as facilitators, motivators, mentors, and evaluators in the learning process. Teacher professionalism, which includes pedagogical, personal, social, and professional competencies, contributes significantly to improving learning effectiveness, student achievement, and the overall quality of education. However, several challenges remain, such as limited training opportunities, unequal educational facilities, and rapid changes in educational demands. Conclusion: Teacher professionalism is a key factor in improving the quality of national education. Therefore, continuous professional development, institutional support, and sustainable training programs are necessary to strengthen teachers’ competencies and support the achievement of quality education.